A Pilot Study on Immunohistochemical Expressions of NF-ĸB, Cyclin-D1, VEGF, and Cox-2 in Advanced Stage Laryngeal Carcinoma - Pudji Rahaju; Ayunita Tri Wirattami; Ferry Sandra; Steffi Kurniawan; Khairun Nisa; Soehartono Soehartono; Edi Handoko; Ahmad Dian Wahyudiono; Hendradi Surjotomo; Hendy Setyo Yudhanto; Nanik Setjowati (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Progression of laryngeal carcinoma can be classified with the clinical staging, however there are different patterns of progressions observed in the patient with the same clinical stage which also affects their prognoses. Therefore biomarkers should be used. Nuclear factor (NF)-ĸB, Cyclin-D1, vascular endothelial growth factor (VEGF), cyclooxygenase (Cox)-2 have been reported for laryngeal carcinoma. However, it is still unclear how these markers are expressed and correlated in advanced stage laryngeal carcinoma. Therefore current study was conducted to investigate the expressions of NF-ĸB, Cyclin-D1, VEGF and Cox-2 and their correlations in advanced stage laryngeal carcinoma.METHODS: Subjects were recruited and laryngeal biopsies were collected, fixed in formalin and prepared for immunohistochemistry. The immunohistochemistry was performed using mouse monoclonal anti-NF-kB p65, anti-Cyclin-D12 anti-VEGF, and anti-Cox-2 antibodies. The immunohistochemistry results were documented and measured using ImmunoRatio. Pearson or Spearman correlation test was used based on the results of Shapiro-Wilk test of normality. A p-value of less than 0.05 is considered statistically significant.RESULTS: Twelve male subjects were included in this study. Expressions of NF-ĸB, Cyclin-D1, VEGF dan Cox-2 were clearly observed. Mean of NF-ĸB, Cyclin-D1, VEGF dan Cox-2 IHC expression levels measured with ImmunoRatio were 57.50±20.06%, 45.00±24.31%, 43.33±17.23% and 40.42±16.98%, respectively. There was significant correlation between the expressions of VEGF dan Cox-2 (p=0.031, r=0.622).CONCLUSION: Since correlation between the VEGF and Cox-2 expressions was statistically significant, VEGF and Cox-2 might have important roles in the growth, invasion and metastasis of laryngeal carcinoma.KEYWORDS: advanced stage laryngeal carcinoma, immunohistochemistry, NF-ĸB, Cyclin-D1, VEGF, Cox-2